Association of cardiovascular disease on cancer: observational and mendelian randomization analyses - Tongtong Bai; Chengyu Wu (Scientific Reports)
Abstract Extensive research is needed to examine the association between cardiovascular disease (CVD) and cancer. The observational study is based on data collected from the 2005–2018 National Health and Nutrition Examination Survey (NHANES). To assess the connection between CVDs and cancer, we used a weighted multivariable logistic regression analysis with as many confounding factors as feasible included in the model. By employing Mendelian randomization (MR), the unbiased causal relationship between CVDs and cancers was ascertained. The primary analytical approach employed the Inverse Variance Weighted methodology. In cross-sectional study, a positive correlation was observed between CVD and cancer (Model 3, Odds ratio 1.26, 95% confidence interval 1.01 ~ 1.57, p = 0.040). However, MR analysis indicated a negative causal relationship between certain subtypes of CVD and specific cancers, with effect sizes for coronary heart disease and lung cancer (β = − 4.759, p = 0.002), breast cancer (β = − 2.684, p = 0.026), colorectal cancer (β = − 4.581, p = 0.042), liver cancers (β = − 19.264, p = 0.028), and stroke with prostate cancer (β = − 0.299, p = 0.017), with no evidence of a positive correlation. Results from the reverse MR causal analysis revealed a positive correlation between prostate cancer and angina pectoris. An observational study linked CVDs risk to cancer risk. MR analysis has shown that the expected incidence of CVDs can reduce the probability of developing certain forms of cancer. Further investigation is required to examine the clinical correlations and underlying processes between these two illnesses.